Halal Tourism Development in East Lombok Regency - Rayendra, Miko (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Abstract The purpose of this study were (1) to determine the perception of tourists on the readiness of halal tourism in East Lombok (2) to analysis a halal tourism development in East Lombok regency with SWOT analysis. Research uses descriptive qualitative method. According Sugiyono (2012) descriptive research is research that seeks describe and interpret data with objective measurements of the phenomenon. In addition, qualitative approach is used because researchers put the theory as the main starting point on the curiosity of researchers to measure the level of preparedness in developing halal tourism in East Lombok. Research aims to describe the potential of halal tourism destinations in East Lombok regency, analysis readiness through perception travel destination travelers in developing halal East Lombok, and clicking the analysis to development of halal tourism. The collection of data, in-depth interviews tourists. results of this study, East Lombok is quite optimal launched halal tourism in its tourism product and still need some improvement ata u strategy to attract tourists.